COGNITIVE BEHAVIOR THERAPY FOR COMORBID OBSESSIVE‐COMPULSIVE DISORDER IN HIGH‐FUNCTIONING AUTISM SPECTRUM DISORDERS: A RANDOMIZED CONTROLLED TRIAL. Issue 8 (6th February 2013) - Russell, Ailsa J.; Jassi, Amita; Fullana, Miguel A.; Mack, Hilary; Johnston, Kate; Heyman, Isobel; Murphy, Declan G.; Mataix‐Cols, David
<x xml:space="preserve">Abstract</x> Background High rates of anxiety disorders, particularly obsessive compulsive disorder (OCD) are reported in people with Autism spectrum disorders (ASD). Group cognitive behavioral treatment (CBT) has been found effective for anxiety in young people with ASD but not been OCD specific. One uncontrolled pilot study of individual CBT for OCD for adults with ASD showed good treatment efficacy. Methods Forty‐six adolescents and adults (mean age 26.9 years, 35 Males) with ASD and comorbid OCD were randomized to CBT for OCD or anxiety management (AM), a plausible control treatment. Treatments were matched in duration (mean of 17.4 sessions CBT; 14.4 sessions AM), the Yale–Brown Obsessive Compulsive Severity Scale (YBOCS) as primary outcome measure and evaluations blind to treatment group. Treatment response was defined as > 25% reduction in YBOCS total severity scores. Results Both treatments produced a significant reduction in OCD symptoms, within‐group effect sizes of 1.01 CBT group and 0.6 for the AM group. There were no statistically significant differences between the two groups at end of treatment, although more responders in the CBT group (45 versus 20%). Effect sizes for self‐rated improvement were small (0.33 CBT group; –0.05 AM group). Mild symptom severity was associated with improvement in the AM but not the CBT group. Family/carer factors were important for both groups, in that increased family accommodation was associated with poorer outcome. Conclusions Evidence‐based psychological interventions, both AM and CBT, were effective in treating comorbid OCD in young people and adults with ASD.